Dampak Teknologi Informasi terhadap Interaksi Sosial Generasi Milenial di Masyarakat melalui Program GKI di Sorong, Papua - Biky, Muhammad Amir; Bantali, Ampun; Arjuna, Achmad; Mutiasari, Dian; Daniswara, Nirwasita (YASIN, 2025)
The purpose of this research is to explore the impact of information technology on the social interaction of the millennial generation, especially in Sorong, Papua based on the GKI programs in Sorong that have been carried out related to the community, especially the millennial generation. The research method used is a qualitative or field method that is strengthened by Systematic Literature Review (SLR) from journals. Field data collection was conducted by interviews and observations and reinforced from SINTA's indexed journals, which discuss topics relevant to empirical data between 2020-2025. The results of the study show that information technology and social media have a significant impact on the millennial generation. GKI's program activities have succeeded in increasing understanding of digital ethics. GKI's program activities have succeeded in increasing understanding of digital ethics. Meanwhile, digital literacy da'wah teaches the wise use of social media and also provides more benefits for the people of Sorong, especially the millennial generation. While social media addiction can increase productivity, it also risks causing anxiety, so the GKI program is a great fit. This is also in line with religious education aimed at strengthening morals, and collaboration between governments, educators, and millennials is needed to create a secure digital ecosystem. The conclusion of this study shows that technological advancements, especially in information technology and social media, greatly affect the millennial generation. GKI's activities have succeeded in increasing awareness of digital ethics for the community, especially millennials in Sorong, Papua. In addition, the impact of this is also felt for those who want to work and study so that it makes it easier.